2022
DOI: 10.1016/j.jceh.2022.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Gut-Barrier Dysfunction in Early Stages of Non-alcoholic Fatty Liver Disease: A Proof-Of-Concept Study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Moreover, in the study of Manka et al it was shown that the protective effects of the anti -TNFα treatment were associated with an improvement of hepatic steatosis in patients with Crohn's Disease [ 52 ]. Somewhat in contrast, in the present study, bacterial endotoxin levels suggested to be indicative of intestinal barrier dysfunction [ 53 ] were significantly higher in SFC-fed mice regardless of strain or treatment when compared with the respective controls. Supporting these findings, xylose permeation in small intestine was also similar between SFC-fed mice, regardless of strain.…”
Section: Discussioncontrasting
confidence: 96%
“…Moreover, in the study of Manka et al it was shown that the protective effects of the anti -TNFα treatment were associated with an improvement of hepatic steatosis in patients with Crohn's Disease [ 52 ]. Somewhat in contrast, in the present study, bacterial endotoxin levels suggested to be indicative of intestinal barrier dysfunction [ 53 ] were significantly higher in SFC-fed mice regardless of strain or treatment when compared with the respective controls. Supporting these findings, xylose permeation in small intestine was also similar between SFC-fed mice, regardless of strain.…”
Section: Discussioncontrasting
confidence: 96%
“…Increased intestinal permeability is a risk factor for type 2 diabetes mellitus and is associated with obesity and nonalcoholic fatty liver disease 194,[197][198][199][200][201] Hyperglycaemia, high-fat diet, nonalcoholic fatty liver disease and obesity are associated with increased intestinal permeability [202][203][204][205][206][207][208] HIV/AIDS Increased permeability in HIV enteropathy; positive correlation with disease stage; increased in patients with untreated HIV infection 90,209,210 Increased intestinal permeability in simian immunodeficiency virus infection is associated with microbial translocation and systemic immune activation 211,212 Multiple organ dysfunction syndrome…”
Section: Boxmentioning
confidence: 99%
“…Growing investigations held the intestinal barrier dysfunction blame for inflaming the NAFLD progression ( Liu et al., 2021 ; Gupta et al., 2022 ; He et al., 2022 ; Leng et al., 2022 ; Kaushal et al., 2022 ; Yu et al., 2022 ). During the initiation and progression of NAFLD, large amounts of gut bacterial metabolites, bacterial components, and other hazards enter the liver through the portal vein due to the intestinal mucosal barrier disruption induced by various stimuli, with the increased intestinal permeability.…”
Section: Roles Of the Gut Microbiota Dysbiosis On Nafld Occurrence An...mentioning
confidence: 99%